Inadvertent Injury of Critical Perforator Vessels during Perforator Flap Surgery - Miyamoto, Shimpei; Sakuraba, Minoru; Nagamatsu, Shogo (Journal of Reconstructive Microsurgery, 2012)
Despite the widespread use of perforator flaps, little has been reported about the inadvertent injury of perforator vessels. We report a retrospective study of the inadvertent injury of perforator vessels. From 1992 through 2010, we transferred 467 free perforator flaps (314 anterolateral thigh [ALT] flaps, 99 fibula osteocutaneous flaps, 46 deep inferior epigastric perforator [DIEP] flaps, and 8 other flaps). Inadvertent injury of perforator vessels occurred in seven patients. The overall incidence was 1.5%. The rate of the injury was 0.95% with ALT flaps, 2.0% with fibula osteocutaneous flaps, and 4.3% with DIEP flaps. Of seven, six flaps were salvaged through anastomosis of the injured perforator vessels. Perforator injuries resulted more often from mishandling of perforator vessels than from dissection technique. Anastomosis of injured perforators is a practical salvage procedure that requires high microsurgical skill.
Keywords: perforator flap; inadvertent injury of perforator vessels; anterolateral thigh flap; deep inferior epigastric artery perforator flap; fibula osteocutaneous flap